2021
DOI: 10.3390/ma14041027
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness and Streptococcus mutans Adhesion on Metallic and Ceramic Fixed Prosthodontic Materials after Scaling

Abstract: The aim of this study was to evaluate the surface roughness of fixed prosthodontic materials after polishing or roughening with a stainless steel curette or ultrasonic scaler and to examine the effect of these on Streptococcus mutans adhesion and biofilm accumulation. Thirty specimens (10 × 10 × 3 mm3) of zirconia (Zr), pressed lithium disilicate (LDS-Press), milled lithium disilicate glazed (LDS-Glaze), titanium grade V (Ti) and cobalt-chromium (CoCr) were divided into three groups (n = 10) according to surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
5
6
0
Order By: Relevance
“…In one of the studies similar results were acquired, showing significantly lower WCA mean value of feldspathic ceramic, compared to Co–Ni–Cr alloy and PMMA, describing all of them as hydrophilic materials 16 . In addition, zirconia and RBC could be considered as hydrophilic and CoCr alloy as barely hydrophobic material 17,18 . Another study revealed significantly higher WCA value of PEEK, which was approximately 90°, as in our research, compared to yttrium‐stabilized tetragonal zirconia (Y‐TZP).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In one of the studies similar results were acquired, showing significantly lower WCA mean value of feldspathic ceramic, compared to Co–Ni–Cr alloy and PMMA, describing all of them as hydrophilic materials 16 . In addition, zirconia and RBC could be considered as hydrophilic and CoCr alloy as barely hydrophobic material 17,18 . Another study revealed significantly higher WCA value of PEEK, which was approximately 90°, as in our research, compared to yttrium‐stabilized tetragonal zirconia (Y‐TZP).…”
Section: Discussionsupporting
confidence: 86%
“…16 In addition, zirconia and RBC could be considered as hydrophilic and CoCr alloy as barely hydrophobic material. 17,18 Another study revealed significantly higher WCA value of PEEK, which was approximately 90 , as in our research, compared to yttrium-stabilized tetragonal zirconia (Y-TZP). However, Y-TZP revealed significantly lower SR value than PEEK, opposite to results from the present study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The first is linked to chitosan’s amino groups, which can be protonated and permeabilize the negatively charged cell membrane, resulting in the destruction and lysis of the internal contents. , Two other coordinated methods are metal chelation and cytoplasmic DNA/mRNA complexation, which decrease intracellular enzyme activity and thus the level of protein synthesis . Even though material roughness is thought to be a critical element in the production of biofilms, when the Ra value is <0.2 μm, the roughness does not affect bacterial adhesion. , Thus, the rougher PEEK-CS will not exhibit increased initial bacterial adhesion. A plaque biofilm, which begins with the initial bacterial adhesion, initiates oral infection.…”
Section: Resultsmentioning
confidence: 99%
“…However, the surface free energy of certain substrates can be changed when in the presence of saliva. According to Hjerppe et al, 54 highly polished lithium disilicate (LDS‐Press) specimens with higher surface free energy values had a similar percentage of bacterial adhesion as Zr, CoCr, and Ti, which are hydrophobic, have higher contact angles, and should theoretically have a lower bacterial adhesion rate. The authors correlated these findings with the ability of the human saliva film to reduce the chemical charge of the surfaces and transform the surface to a more hydrophilic pattern.…”
Section: Discussionmentioning
confidence: 99%